Comparing the Learning Material and Lesson Plan Designed for Teaching Arabic and English Curriculums and Exploring the Possibility of Conjoining the Textbooks Lesson Themes - Al-Hozali, Futoon (Education and Linguistics Research, 2024)
This research observes Arabic and English language curriculums adopted in a private school which follows a cooperative and communicative language teaching approach. The research reveals the similarities and differences found in the textbooks and classroom procedures via analyzing the Arabic and English curriculums implemented in a private school. Additionally, the researcher suggests, based on their observation, the possibility of conjoining the topics and themes of both language courses.